Delayed recurrent pleuropericardial effusions following atrial septal defect closure with Amplatzer septal occluder device: a case of postpericardiotomy syndrome?. (8th May 2018) - Kwok, Grace, GHTK; Witts, Rachel; Frigiola, Alessandra
Abstract : The authors present the case of a 41-year-old woman, who presented with moderate pericardial effusion and bilateral pleural effusion 11 months following a secundum atrial septal defect closure with an Amplatzer septal occluder (ASO) device. The acute presentation responded well to diuretics and a short course of corticosteroid therapy. The patient, however, continued to experience pleuritic chest pain and a recurrence of pericardial effusion a month later. The patient showed significant symptomatic improvement with a 2-month course of down-titrating prednisolone. Six months later, the echocardiogram showed complete remission of pleural and pericardial effusion. The possibility of cardiac erosion following ASO implantation has been excluded. The aetiology of the reoccurrence of steroid-responsive pleuropericarditis remains unknown.